STUDI KASUS PEMEROLEHAN KANJI BAHASA JEPANG PADA MAHASISWA SEMESTER II TAHUN AJARAN 2022/2023 - Alif Indrian, Nizar (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2023)
This research aims to discover how well are acquisition of Kanji among new students of the State University of Jakarta’s Japanese Language Education Study Program and how motivation, self-confidence, and anxiety affect it. Based on a preliminary study held, Kanji is regarded to be the most difficult part to master in Japanese. Thus, the focus of this research will be about the acquisition of Kanji. This research uses a case study method and will acquire data through interviews and documentations on five students who have never previously learned Japanese. Results show only one student has undergone the proses of acquiring Kanji before entering the Japanese Langauge Education Study Program. Furthermore, looking at the students’ learning process, it is known that three use only textbooks, while two use other sources for studying. Viewing from the aspect of factors that affect language acquisition, one student has motivation, self-confidence, and does not have anxiety. While the other four students have motivation, but does not have self-confidence, and has anxiety. It is also known from their grades that all five students have above average scores in Kanji, thus it can be concluded that motivation has a bigger role compared to self-confidence and anxiety.